PENCEGAHAN PENYEBARAN VIRUS CORONA DI KABUPATEN SUMBAWA - Wahyudi, Agus; Martadinata, Sudrajat; Levia Tryana, Ayu; Mandasari, Jayanti; Nurfadliyah, Nurfadliyah; Reno Kemala Sari, Putri; Komala, Rina (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
Sumbawa Regency is one of the ten districts/cities in the West Nusa Tenggara Province. As of April 20, 2020, 8 people have tested positive for the corona virus. The spread of the corona virus has made lecturers of the Accounting Study Program and the Management Study Program of the Faculty of Economics and Business, University of Technology of Sumbawa, to contribute by distributing masks and promoting healthy lifestyles in the face of the spread of the corona/Covid-19 virus. The activity was carried out around Jalan Setia Budi, Seketeng Market Area, and several points in the Sumbawa District.